Ideas on personality: a contrastive analysis between Iqbal & Freud - Abdul Razak, Mohd Abbas (2015)
The subject on man and personality is one that has been discussed over the centuries. This topic has caught the attention of many scholars of diverse specialization in the East and West. The studies conducted on man, be it in the areas of psychology, biology, religion, history, anthropology, sociology, humanities, etc, are all aimed at exploring the yet undiscovered areas of his nature and potentials. Researchers believe that any latest findings on man will be added information to the existing knowledge and science on man. It is believed that such information can be beneficial in solving many of the problems faced by modern man who lives in an ever-changing world. Idealistically it is thought that solutions found in overcoming man’s problems, are expected to improve his quality of life and his state of psychological well being as an individual coexisting with others, including the flora and fauna. The present study in the area of philosophical psychology is an attempt to explore, investigate and analyze the ideas of two renowned scholars originating from two different parts of the world. Very specifically the researcher would like to investigate the ideas of Muhammad Iqbal (1879-1938) and Sigmund Freud (1856-1939) pertaining to their concepts on man and personality. Iqbal and Freud wrote and lectured on the hidden forces of the human psyche. The fact that they believed that the inner dimension of man particularly the ego, which plays a pivotal role in all human behaviour and personality, draws the attention of the researcher to explore their concept on the human psyche, and on how personality development takes place in individuals. The crux of this study is aimed at conducting a contrastive analysis on the theories presented by Iqbal and Freud.